2019
DOI: 10.5194/angeo-2019-15
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of latitudinally displaced gravity wave forcing in the lower stratosphere on the polar vortex stability

Abstract: Abstract. In order to investigate the impact of a locally confined gravity wave (GW) hotspot, a sensitivity study based on simulations of the middle atmosphere circulation during northern winter was performed with a nonlinear, mechanistic, global circulation model. To this end, for the hotspot region we selected a fixed longitude range in the East Asian region (120° E–170° E) and a latitude range from 22.5° N–52.5° N between 18 km and 30 km, which was then shifted northward in steps of 5°. For the southernmost… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
3
4
0
Order By: Relevance
“…S2), which is flanked by two patches of enhanced EPfd. This can be attributed to a missing impact of OGWD above the subtropical jet, because similar anomalies of the EPfd have been documented in idealised model studies by Šácha et al (2016) and Samtleben et al (2019). In those studies, artificially injected GWD in this region inhibits the upward and equatorward PW propagation from the mid latitudes and focuses the PWs poleward creating an EPfd anomaly in the polar region.…”
Section: Dynamics and Circulationsupporting
confidence: 62%
“…S2), which is flanked by two patches of enhanced EPfd. This can be attributed to a missing impact of OGWD above the subtropical jet, because similar anomalies of the EPfd have been documented in idealised model studies by Šácha et al (2016) and Samtleben et al (2019). In those studies, artificially injected GWD in this region inhibits the upward and equatorward PW propagation from the mid latitudes and focuses the PWs poleward creating an EPfd anomaly in the polar region.…”
Section: Dynamics and Circulationsupporting
confidence: 62%
“…For the RM hotspot, a suppressed upward propagation of resolved waves throughout the stratosphere leads to significant positive EPFD anomalies, but only near the stratopause (and continuing to the mesosphere, see Figures S3a-S3c). The diversity of the resolved wave anomalies in the stratosphere dependent on the hotspot is in agreement with mechanistic model studies with artificial OGWD enhancements (see Šácha et al, 2016 for the EA hotspot and Samtleben et al, 2019Samtleben et al, , 2020. This indicates that the anomalous resolved wave propagation starting from the lower stratosphere is directly caused by the strong OGWD events and not by the "hotspot preconditioning".…”
Section: Resultssupporting
confidence: 84%
“…Since the advent of the so-called wave driving paradigm (Holton et al, 1995) the dynamical effect of OGWs in models has been increasingly evaluated as a contribution to the driving of the advective Brewer-Dobson circulation (BDC; Butchart, 2014;Sato & Hirano, 2019). Another OGW impact that received considerable attention is connected to sudden stratospheric warming (SSW) events (Baldwin et al, 2020), either via the SSW preconditioning and triggering (Albers & Birner, 2014;Richter et al, 2010;Šácha et al, 2016;Samtleben et al, 2019Samtleben et al, , 2020 or the vortex recovery (Limpasuvan et al, 2012). Cohen et al (2013) showed that perturbations to OGW forcing become balanced by changes in resolved wave drag in a mechanistic model, and Cohen et al (2014) showed further that the response fully develops on a time-scale of days.…”
mentioning
confidence: 99%
“…Since the advent of the so-called wave driving paradigm (Holton et al, 1995) the dynamical effect of OGWs in models has been increasingly evaluated as a contribution to the driving of the advective Brewer-Dobson circulation (BDC; Butchart, 2014;Sato & Hirano, 2019). Another OGW impact that received considerable attention is connected to sudden stratospheric warming (SSW) events (Baldwin et al, 2020), either via the SSW preconditioning and triggering (Albers & Birner, 2014;Richter et al, 2010;Šácha et al, 2016;Samtleben et al, 2019Samtleben et al, , 2020 or the vortex recovery (Limpasuvan et al, 2012). Cohen et al (2013) showed that perturbations to OGW forcing become balanced by changes in resolved wave drag in a mechanistic model, and Cohen et al (2014) showed further that the response fully develops on a time-scale of days.…”
mentioning
confidence: 99%
“…It includes RW sourcing by instabilities induced by OGW drag (OGWD) (McLandress & McFarlane, 1993;Sato et al, 2018;Smith, 2003), OGWD impact on RW breaking in the surf zone and the alteration of resolved wave propagation through modification of the background winds (Sigmond & Scinocca, 2010). Further, it has been demonstrated that the OGWD impact on resolved wave fields depends on the spatio-temporal OGWD distribution (Boos & Shaw, 2013;Šácha et al, 2016;Shaw & Boos, 2012) and specifically on the location of OGWD relative to the stationary planetary scale RWs (Samtleben et al, 2019(Samtleben et al, , 2020. Shepherd (2014) highlighted the interaction between parameterized GWs and the large-scale circulation as one of the most uncertain aspects of climate modeling.…”
mentioning
confidence: 99%